2011
DOI: 10.1259/bjr/97507379
|View full text |Cite
|
Sign up to set email alerts
|

Development of an imaging-planning program for screen/film and computed radiography mammography for breasts with short chest wall to nipple distance

Abstract: Objective: Imaging breasts with a short chest wall to nipple distance (CWND) using a traditional mammographic X-ray unit is a technical challenge for mammographers. The purpose of this study is the development of an imaging-planning program to assist in determination of imaging parameters of screen/film (SF) and computed radiography (CR) mammography for short CWND breasts. Methods: A traditional mammographic X-ray unit (Mammomat 3000, Siemens, Munich, Germany) was employed. The imaging-planning program was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Many studies 9,16,19,20 have reported techniques for correcting the CBT records obtained from imaging procedures. The CBT correction technique used in this study is identical to that in our previous studies 12,21 and is similar to the technique reported by Kruger and Schueler. 9 A 6-cm-thick BR-12 phantom (Nuclear Associates, Carle Place, NY) was used, and various forces were applied.…”
Section: Iib Cbt Correctionsupporting
confidence: 53%
“…Many studies 9,16,19,20 have reported techniques for correcting the CBT records obtained from imaging procedures. The CBT correction technique used in this study is identical to that in our previous studies 12,21 and is similar to the technique reported by Kruger and Schueler. 9 A 6-cm-thick BR-12 phantom (Nuclear Associates, Carle Place, NY) was used, and various forces were applied.…”
Section: Iib Cbt Correctionsupporting
confidence: 53%